Chemotherapy combined with endocrine neoadjuvant therapy for hormone receptor-positive local advanced breast cancer: a case report and literature review - Zhang, Nengying; Luo, Chengmin; Li, Jiayang; Bao, Yuxiang; Yan, Zhongliang; Cheng, Xiaoming; Li, Taolang; Lv, Junyuan (Frontiers in Endocrinology, 2024)
Background Early studies have revealed antagonistic effects associated with stacking chemotherapy (CT) and endocrine therapy (ET), thereby conventional wisdom does not advocate the simultaneous combination of these two treatment modalities. Limited clinical studies exist on the combined use of neoadjuvant CT (NACT) and neoadjuvant ET (NET), and there are no reported instances of concurrent neoadjuvant treatment for locally advanced breast cancer (LABC) using capecitabine and fulvestrant (FUL). Case presentation We reported a 54-year-old woman who was diagnosed with hormone receptor-positive (HR+) LABC at our hospital. After neoadjuvant treatment involving two distinct CT regimens did not lead to tumor regression. Consequently, the patient was transitioned to concurrent capecitabine and FUL therapy. This change resulted in favorable pathological remission without any significant adverse events during treatment. Conclusions A novel approach involving concurrent neoadjuvant therapy with CT and endocrine therapy may offer a potentially effective treatment avenue for some cases with HR+ LABC.